The effect of exchange rate, inflation, interest rate and import on exports in ASEAN countries - Yuliadi, Imamudin; Sari, Noni Pradika; Setiawati, Sri Ani Puji; Ismail, Syadan Hussein (Jurnal Ekonomi & Studi Pembangunan, 2024)
Export is one sector of the economy with a major role through market expansion between several countries, where it can carry out an expansion in an industry, thereby encouraging other industries and further encouraging other sectors of the economy. This study aims to analyze the effect of exchange rates, inflation, interest rates, and imports on exports in ASEAN countries. The data used in this study were annual data for the 2015-2019 period sourced from the World Bank. This research model employed a panel data method with a fixed-effect model, combining time series and cross section data with the help of EViews 7. The results revealed that exchange rates and imports had a positive and significant effect on exports. In addition, inflation and interest rates had a positive and insignificant effect on exports. Therefore, the governments of the ASEAN countries must monitor the stability of exchange rates, inflation, interest rates, and imports to increase exports from year to year so that the economy in ASEAN countries remains stable.